Increasing vulnerability to floods in new development areas: evidence from Ho Chi Minh City. Issue 1 (28th September 2017) - Duy, Phan N.; Chapman, Lee; Tight, Miles; Linh, Phan N.; Thuong, Le V.
Abstract : Purpose: Flooding is an emerging problem in Ho Chi Minh City (HCMC), Vietnam, and is fast becoming a major barrier to its ongoing development. While flooding is presently of nuisance value, there is a growing concern that a combination of rapid urban expansion and climate changes will significantly exacerbate the problem. There has been a trend of population being rapidly accommodated in new urban areas, which are considered highly vulnerable to floods, while the development strategy by the local government still attracts more property investments into the three new districts on the right side of Saigon River. This paper aims to discuss the increase in the number of residences vulnerable to flooding, to underline the need for more appropriate future spatial development. For the vision, an application of compact and resilient theories to strategic planning and management of this city is proposed to reduce vulnerability. This paper also highlights the need to better understand growing vulnerability to floods related to urban expansion over low-lying former wetlands and the more important role of planning spatial development accompanied with transportation investment which can contribute to flooding resilience. Design/methodology/approach: This research uses combined-methods geographical information system (GIS) analysis based on secondary data of flood records, population distributions, property development (with the details of 270 housing projects compiled as part of this research) and flooding simulation. This allows an integrated approach to the theories of urban resilience and compactness to discuss the implication of spatial planning and management in relevance to flooding vulnerability. Findings: The flooding situation in HCMC is an evidence of inappropriate urban expansion leading to increase in flooding vulnerability. Although climate change impacts are obvious, the rapid population growth and associated accommodation development are believed to be the key cause which has not been solved. It was found that the three new emerging districts (District 2, 9 and ThuDuc) are highly vulnerable to floods, but the local government still implements the plan for attracted investments in housing without an integrated flooding management. This is also in line with the development pattern of many coastal cities in Southeast Asia, as economic development can be seen as a driving factor. Research limitations/implications: The data of property development are diversified from different sources which have been compiled by this research from the basic map of housing investments from a governmental body, the Department of Construction. The number of projects was limited to 270 per over 500 projects, but this still sufficiently supports the evidence of increasing accommodation in new development districts. Practical implications: HCMC needs neater strategies for planning and management of spatial development to minimize the areas vulnerable to floods: creating more compact spaces in the central areas (Zone 1) protected by the current flooding management system, and offering more resilient spaces for new development areas (Zone 2), by improving the resilience of transportation system. Nevertheless, a similar combination of compact spaces and resilient spaces in emerging districts could also be incorporated into the existing developments, and sustainable drainage systems or underground water storage in buildings could also be included in the design to compensate for the former wetlands lost. Social implications: This paper highlights the need to better understand growing vulnerability to floods related to urban expansion over low-lying former wetlands and emphasizes the more important role of planning spatial development accompanied with transportation investment which can contribute to flooding resilience. Coastal cities in southeast countries need to utilize the former-land, whereas feasibility of new land for urban expansion needs to be thoroughly considered under risk of natural disasters. Originality/value: A combination of compact spaces with improved urban resilience is an alternative approach to decrease the flooding risk beyond that of traditional resistant systems and underlines the increasingly important role of urban planning and management to combat the future impacts of floods.